Digital Application and Software Adoption for Financial Planning: Evidence from Small and Medium Enterprises in Kathmandu Valley - Ojha, Gaurav; Dongol, Padam; Maharjan, Aliza (The Batuk, 2026)
This paper examines the influence of ease of use, data security concerns, awareness, the cost of digital applications, and the technical support on the adoption of digital applications for financial planning in small and medium size enterprises (SMEs) in Kathmandu valley. This study has applied quantitative cross-sectional research methods for collecting quantitative data from 67 SMEs inside Kathmandu Valley with a sample size of 165 respondents associated with the account/finance department and involved in financial planning and decision-making. Results of this study indicate that ease of use and technical support availability are the predictors of digital applications adoptions among SMEs, whereas cost of digital applications data security and privacy concerns, and awareness are barriers to implementation of these applications for financial planning. Based on the findings, this study suggests software developers, suppliers, dealers and service providers of digital applications used for financial planning and management to prioritize user-friendly, easy-to-use features; focus on cost-effective applications; design training and awareness programs; and ensure access to adequate technical support to maximize adoption of their products among SMEs in the Kathmandu Valley.